Development of smart energy towns in China: Concept and practices. (March 2020) - Liang, Xuesheng; Ma, Linwei; Chong, Chinhao; Li, Zheng; Ni, Weidou
Abstract: With increasing needs for the development of both smart cities and smart energy systems, the intersection concept of smart energy city (SEC) have been emerged in recent years. However, there is still lack of discussions on this concept with the background of developing countries. With serious challenges of urbanization and energy, China can provide a prominent case to further deep the understanding of this concept in the background of a rapidly developing country. This manuscript aims to propose and define a new concept of smart energy towns (SET) according to recent theoretical progress and China's practical experience on SEC. First, we reviewed the connotations of smart city, smart energy systems, and smart energy city, and then derive a definition of SET according to China's national conditions. Second, we introduced the status quo of SET projects in China, and identify the gaps and barriers to development SET as compared with the definition. Finally, from the view of four stakeholders, including China's central government, international organization, China's regional government, and enterprises, we put forward some actions recommendations for the development of China's SET. The main findings are that compared with SEC, SET emphasizes the importance of overall planning of energy and urbanization, as well as promoting business model innovation to support economic development. The main barriers to the development of SET in China lies in the lack of planning and policy support for local projects by regional governments, as well as the lack of funds and capacity of local enterprises to carry out project construction. To this end, stakeholders must work together to help cities and towns strengthen project planning and policy research, as well as jointly strengthen investment and explore practical business models suitable for each region to promote the development of SET in China. Highlights: Concept models of global smart cities and smart energy systems were reviewed. A definition of smart energy town is given by the case study of China. Objectives and driving forces of current smart energy town projects were determined. Gaps and barriers to build smart energy towns in China were investigated. Action recommendations for various stakeholders are put forward.